DEGRADASI PENGGUNAAN BAHASA JAWA KRAMA INGGIL DI SEKOLAH DASAR KABUPATEN BLITAR: FAKTOR PENYEBAB DAN UPAYA PELESTARIAN DI ERA DIGITAL - Biassari, Icha; Yulianti, Anggun; Wasino; Aricindy, Argitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The decline in the use of Bahasa Jawa Krama Inggil among elementary school students has become an important issue in preserving local wisdom amid the increasingly pervasive digital era. This condition indicates a shift in language practices that may reduce the values of politeness and Javanese cultural identity among the younger generation. This study aims to analyze the use of Bahasa Jawa Krama Inggil, identify the factors contributing to its decline, and examine preservation efforts in elementary schools in Blitar Regency. This research employs a descriptive qualitative method, with data collection techniques including observation, interviews, and documentation conducted in five public elementary schools in Blitar Regency. The research participants consisted of five principals, ten Javanese language teachers, and thirty students selected purposively. Data were analyzed through systematic stages of data reduction, data display, and conclusion drawing. The results indicate that most students predominantly use the ngoko variety in daily communication, including when interacting with teachers, such as using the term “sampean” instead of “panjenengan.” This decline is influenced by three main factors: family environments that do not habituate the use of krama, school learning processes that remain largely theoretical, and the influence of digital media dominated by Indonesian and foreign languages. Preservation efforts include habituation of language use in schools, integration of local wisdom values into learning, and collaboration among families, schools, government, and communities. These findings highlight the importance of a comprehensive and adaptive approach, including the wise use of technology as a medium for cultural preservation.